Investigation of Wave Propagation in a Nonlinear Dispersive Transmission Line - Tunçay, Ali Ayhan; Yaraneri, Halil (İstanbul Kültür Üniversitesi Yayınları, 2006)
Nonlinear wave propagation in a nonlinear dispersive LC transmission line with linear inductance and nonlinear capacitance (vericap diode) is investigated. Dispersion in the line is introduced by second nearest neighbor interaction and contorlled by reverse bias voltage. Waves at tehe region of group velovity despersion are seen to be modulationally unstable and tihs leads to chaos wiht increase of wave amplitude. Emergence of chaos is investigated by Fourier and time-domain analyses, and via numerical simulations.

Lineer bir bobin ve lineer olmayan bir kondansatörden (verikap diyot) oluşan lineer olmayan dağınımlı bir LC iletim hattındaki lineer olmayan dalga yalımı incelendi. Hattaki dağınım, ikinci yakın komşu etkileşimi ile oluşturuldu ve diyota uygulanan ters öngerilim ile kontrol edildi. Grup hızı dağınımı bölgesindeki dalgaların modülasyona karşı kararsız olduğu ve bunun dalga genliğinin artmasıyla kaosa gittiği görüldü. Kaos’un ortaya çıkışı Fourier ve zaman bölgesi analizleri ve sayısal simülasyonlar yoluyla incelendi.
Keywords: Wave Propagation; Nonlinear Transmission Line; Modulational Instability; Chaos; Dalga Yayılımı; Doğrusal Olmayan İletim Hattı; Modulational Instabilite; Kaos